Exploring innovative G-CSF schedules in AML cytarabine-based consolidation through a digital twin study of white blood cell recovery - Adrian-Manuel Reimann; Enrico Schalk; Dimitrios Mougiakakos; Thomas Fischer; Sebastian Sager (PLoS ONE, 2026)
Patients with acute myeloid leukemia (AML) are at high risk for life-threatening infectious complications due to chemotherapy-induced leukopenia. In contrast to other malignancies, prophylactic administration of granulocyte colony-stimulating factors (G-CSF) is not routinely done in AML. However, recently, clinical trials showed that administration of G-CSF post consolidation chemotherapy leads to faster white blood cell (WBC) recovery and to fewer infections. We investigated novel G-CSF schedules using a mathematical model trained with retrospective clinical data (digital twins) consisting of high-frequency measurements of 65 patients. We evaluated 323 different treatments varying in start and duration of G-CSF administration by examining the impact on the occurrence and duration of leukopenia. For each treatment, we used the same 65 digital twins, plus an additional 100 artificial patients for uncertainty quantification, receiving 3 consolidation cycles each. We lumped the 323 treatments into 4 clusters: NO-G-CSF, PRE-G-CSF, SIM-G-CSF, and POST-G-CSF for schedules without G-CSF, that terminated G-CSF before consolidation chemotherapy started, that overlapped on at least one day, and that started post chemotherapy, respectively. The numerical simulations resulted in substantial differences in the occurrence of leukopenia: 88% of all consolidation cycles with leukopenia for NO-G-CSF, 98% for SIM-G-CSF, 45% for POST-G-CSF, and 28% for PRE-G-CSF. Administration of G-CSF before chemotherapy may thus significantly enhance the efficacy of AML consolidation therapy and, therefore, warrants clinical investigation.